MENINGKATKAN ELEKTRIFIKASI LOKASI REMOTE AREA DENGAN KONVERSI GETARAN MENJADI LAMPU PENERANGAN BERBASIS PIEZOELEKTRIK - Azizi, Muhammad Kamal (Jurnal Teknologi Terpadu, 2024)
In District 2 Banyu Asin (BNA) Pertamina Field Cepu there are 2 wells that function as Pumping Units (PU). This Pumping Unit uses an artificial Pumping Unit system with a Gas Engine. The location of these 2 pump-ing wells is very far from the source of the electricity network provided by PLN, so that for the operation of urgent lighting needs, generators are still used. The generator used has had a history of trouble which caused the power source to experience blackouts. This results in additional problems in operating the Pumping Unit if the generator power goes out at night. This study uses piezoelectricity, which is a component that can accumu-late an electric charge as a result of mechanical pressure. The energy generated by the piezoelectric will be stored in the battery via a boost converter. The battery will supply voltage and current to the lamp which will illuminate the location. In the process of charging the battery, the voltage will be stabilized by the PID system. The PID system will use the zieger nichols 2 method.